Analyzing structure–function relationships of artificial and cancer-associated PARP1 variants by reconstituting TALEN-generated HeLa PARP1 knock-out cells. Issue 21 (29th September 2016) - Rank, Lisa; Veith, Sebastian; Gwosch, Eva C.; Demgenski, Janine; Ganz, Magdalena; Jongmans, Marjolijn C.; Vogel, Christopher; Fischbach, Arthur; Buerger, Stefanie; Fischer, Jan M.F.; Zubel, Tabea; Stier, Anna; et al.
Abstract: Genotoxic stress activates PARP1, resulting in the post-translational modification of proteins with poly(ADP-ribose) (PAR). We genetically deleted PARP1 in one of the most widely used human cell systems, i.e. HeLa cells, via TALEN-mediated gene targeting. After comprehensive characterization of these cells during genotoxic stress, we analyzed structure–function relationships of PARP1 by reconstituting PARP1 KO cells with a series of PARP1 variants. Firstly, we verified that the PARP1\E988K mutant exhibits mono-ADP-ribosylation activity and we demonstrate that the PARP1Ł713F mutant is constitutively active in cells. Secondly, both mutants exhibit distinct recruitment kinetics to sites of laser-induced DNA damage, which can potentially be attributed to non-covalent PARP1–PAR interaction via several PAR binding motifs. Thirdly, both mutants had distinct functional consequences in cellular patho-physiology, i.e. PARP1Ł713F expression triggered apoptosis, whereas PARP1\E988K reconstitution caused a DNA-damage-induced G2 arrest. Importantly, both effects could be rescued by PARP inhibitor treatment, indicating distinct cellular consequences of constitutive PARylation and mono(ADP-ribosyl)ation. Finally, we demonstrate that the cancer-associated PARP1 SNP variant (V762A) as well as a newly identified inherited PARP1 mutation (F304L\V762A) present in a patient with pediatric colorectal carcinoma exhibit altered biochemical and cellular properties, thereby potentially supporting human carcinogenesis. Together, we establish a novel cellular model for PARylation research, by revealing strong structure–function relationships of natural and artificial PARP1 variants.